2015
DOI: 10.9789/2175-5361.2015.v7i5.145-154
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the family caregiver of dependent elderly in home living Perfil do cuidador familiar de idosos dependentes em convívio domiciliar

Abstract: Objetivo: identificar o perfil do cuidador familiar de idosos dependentes em convívio domiciliar, no município de João Pessoa – PB, de acordo com as características sociodemográficas, informações referentes à demanda de cuidado e ao suporte de ajuda para o desempenho do cuidado. Método: estudo epidemiológico em que participaram 52 cuidadores familiares de idosos dependentes. A coleta de dados foi realizada mediante entrevistas domiciliares. Resultados: verificou-se maior predominância de cuidadores do sexo fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Research evidences a scenario of older adult women in the role of being informal caregivers for relatives with impaired functional capacity (2)(3) . A national study aimed at identifying the family caregiver profile of dependent persons at home found that among the 52 participants, the majority (96.2%) were women, and about 31% were between 61 and 80 years old (2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research evidences a scenario of older adult women in the role of being informal caregivers for relatives with impaired functional capacity (2)(3) . A national study aimed at identifying the family caregiver profile of dependent persons at home found that among the 52 participants, the majority (96.2%) were women, and about 31% were between 61 and 80 years old (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Research evidences a scenario of older adult women in the role of being informal caregivers for relatives with impaired functional capacity (2)(3) . A national study aimed at identifying the family caregiver profile of dependent persons at home found that among the 52 participants, the majority (96.2%) were women, and about 31% were between 61 and 80 years old (2) . In corroborating the greater number of women exercising the caregiver role, research justifies that care is a function that is socially attributed to the feminine personality, and is therefore a social construct (3) .…”
Section: Introductionmentioning
confidence: 99%
“…As dificuldades para realização de atividades de higiene, transferência, mudança de decúbito e outras que exigem força, embora essenciais para a saúde dos sujeitos cuidados, revelaram-se as mais desgastantes e que requerem auxílio de outro familiar (83) . No entanto, a maioria das cuidadoras familiares principais obtém mais ajuda para atividades menos instrumentais e com menores níveis de dificuldade, que não exigem muito esforços físicos (99) . Estudo realizado com cuidadoras familiares evidenciou que 60,3% recebiam apoio de outras pessoas para cuidar do idoso, citando principalmente os membros familiares: filho do idoso (24,1%), filho das cuidadoras familiares (17,2%), assim como vizinho (8,6%); e 39,7% não recebiam apoio informal (5) .…”
Section: Discussionunclassified
“…[ 8 ] superior incompleto (graduação ou tecnológico incompleto) [ 9 ] superior completo (graduação ou tecnológico completo) [10] especialização de nível superior (mínimo de 360 horas) [11] mestrado [12] [ 0 ] Hospital público/ambulatórios [ 1 ] Consultório particular ou clínica privada [ 2 ] Unidade Básica de Saúde [ 3 ] Centros de especialidades (Policlínicas) [ 4 ] Unidade de pronto atendimento ou emergência de hospital público [ 5 ] Unidade de pronto atendimento ou emergência de hospital particular [ 6 ] Conhecido [99] NS/NR 140 13.21. Que tipo de serviços de saúde o(a) Sr. (a) X utiliza?…”
Section: Conclusõesunclassified
See 1 more Smart Citation